The effect of insulin and kruppel like factor 10 on osteoblasts in the dental implant osseointegration in diabetes mellitus patients. Issue 6 (1st June 2022) - Sheng, Chen; Guo, Yalin; Hou, Wenjie; Chen, Haobin; Liu, Hongchen; Wang, Lin
ABSTRACT: Diabetes mellitus, metabolic disease, is characterized by chronic hyperglycemia. Patients with diabetes mellitus are susceptible to infection and therefore have a higher prevalence and progression rate of periodontal disease. We aimed to study the effect of insulin and kruppel like factor 10 (KLF10) on osteoblasts proliferation and differentiation, and expression of bone metabolism-related molecules and related signaling pathway molecules of AKT serine/threonine kinase 1 (AKT) and nuclear factor kappa B subunit 1 (NF-κB) through in vitro experiments, which can provide theoretical basis for the dental implant osseointegration in diabetic patients. The osteoblasts (hFOB 1.19 cells) were subdivided into KLF10 gene over expression group, KLF10 gene knockdown group, and KLF10 gene knockdown + insulin treatment group. CCK-8 and ELISA were, respectively, used for analysis of cell proliferation and differentiation. In vitro experiments were applied to detect the mRNA and protein expression of bone metabolism-related molecules, respectively. GSE178351 dataset and GSE156993 dataset were utilized to explore the expression of KLF10 in periodontitis. In osteoblasts, insulin treatment increased the expression of KLF10. Insulin and KLF10 could reduce the proliferation and differentiation of osteoblasts. Knockdown of KLF10 could increase the expression of bone metabolism-related molecules and activate AKT and NF-κB pathways, whereas insulin reversed this effect. KLF10 was up-regulated in both patients with periodontitis and type 2 diabetes mellitus with periodontitis. It is assumed that knockdown of KLF10 in insulin resistance may promote osteoblasts differentiation and dental implant osseointegration in diabetic patients. Graphical Abstract: uf0001